A Study to Assess the Prevalence and Risk Factors of Hypertension among the Bank Employees of Rajkot City, Gujarat, India - Nikita M Savani; Rajendra B Chauhan; Rajesh K Chudasama (Medsci Publications, 2020)
Background: Hypertension (HTN) is a modifiable and major risk factor for coronary artery disease, heart failure, cerebrovascular disease and chronic renal failure. Present study conducted to study the prevalence of hypertension among bank employees of Rajkot city and to study the associated risk factors of hypertension among them. Methods: Rajkot city has around 160 different bank branches, including 35 private and 125 nationalized bank branches. Total 70 bank branches selected including all 35 private and similar number of nationalized bank branches (35) by using systemic random sampling. The present study was conducted from January to December 2017. Information regarding demographic profile and risk factors of hypertension was collected on pretested proforma. Results: Out of total 800 employees, prevalence of hypertension was found 30.4% including 7.6% self reported and 22.8% detected in the study. Highest prevalence of hypertension was reported in 50-59 years age group followed by 20-29 years (26.3%). Hypertension found more among male (90.9%) and work experience less than 10 years (42.8%). Significant association found on assessing risk factors like history of addiction, not doing any physical exercise, obesity, high BMI and hypertension. Conclusion: Hypertension was reported more in elder age group and Males among bank employees. Age and sex were found significantly associated with hypertension. Addiction (tobacco and alcohol), not doing any physical exercise, central obesity and high BMI status found significant risk factors for hypertension.